2010
DOI: 10.1002/mnfr.200900329
|View full text |Cite
|
Sign up to set email alerts
|

Ingested quercetin but not rutin increases accumulation of hepatic β‐carotene in BALB/c mice

Abstract: Beta-carotene is a carotenoid with a range of reported health benefits besides vitamin A activity. If the enzymatic conversion of beta-carotene to retinal is suppressed in the digestive tract, residual beta-carotene that reaches the tissues increases. We evaluated the function of quercetin and rutin (quercetin-3-rutinoside) to increase the accumulation of beta-carotene in vitro and in vivo in BALB/c mice. When the conversion of beta-carotene by a preparation of the murine small intestine was measured in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…A study revealed that luteolin, quercetin, and rutin, active compounds in CM, may noncompetitively inhibit the activity of β‐carotene‐15, 15′‐monooxygenase extracted from intestine (Nagao and others 2000). Feeding with diet containing quercetin or rutin did not alter level of hepatic retinol in BALB/mice, but decreased level of hepatic retinoic acid (Bando and others 2010). This suggested that more β‐carotene absorbed might be converted to retinol.…”
Section: Resultsmentioning
confidence: 97%
“…A study revealed that luteolin, quercetin, and rutin, active compounds in CM, may noncompetitively inhibit the activity of β‐carotene‐15, 15′‐monooxygenase extracted from intestine (Nagao and others 2000). Feeding with diet containing quercetin or rutin did not alter level of hepatic retinol in BALB/mice, but decreased level of hepatic retinoic acid (Bando and others 2010). This suggested that more β‐carotene absorbed might be converted to retinol.…”
Section: Resultsmentioning
confidence: 97%
“…The antioxidant interactions and the bioavailability interactions among phytochemicals were often measured independently, however, rare study investigated their correlation [ 23 ]. Several studies have revealed the role of flavonoids in the cell uptake of carotenoids without further determining their influence on the biological effects of carotenoids [ 11 , 24 , 25 , 26 ]. The absorption, distribution, and metabolism of carotenoids varied in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the detected lycopene and lutein content is lower in L-02 cells than in Caco-2 cells. Flavonoids were considered to interfere with the absorption of carotenoids in several studies [ 11 , 12 , 24 , 25 , 26 , 29 ]. In the case of naringenin and lutein, competition between them for cellular uptake led to the reduced lutein uptake in vivo [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased hormone level can be explained by its inhibitory effect produced on Thyroid peroxidase enyzme (TPO) ( Metodiewa et al, 1997) rutin is also an antioxidant compared to quercetin, acacetin, morin, hispidulin, hesperidin, and naringin, it was found to be the strongest ( Bando et al, 2010) Siddiqui (1998) survey makes reference to eighteen flavonoids including glycosides of quercetin (rutin) and isorhamnetin. Mata et al (1991) and colleagues segregated sakuranetin from Mexican D. viscosa in 1991. it is a yellow crystalline solid that has been used to dye wool (Fig.4) (Mabry, 1970).…”
Section: Discussionmentioning
confidence: 99%